Mechanistic-empirical approach for design of low volume pavements - Gupta A.; Kumar P.; Rastogi R. (My University, 2025)
This study proposes a more rational method to design low-volume roads (LVRs), which accounts for permanent deformation development in granular layers. Rutting is regarded as the main distress mode in unsealed and thinly sealed pavements. Hence, it is desirable that it be analytically approached rather than empirically. Twenty low-volume pavement sections from West Uttar Pradesh and Uttarakhand regions were considered for full scale in situ tests conducted annually for the period of 4 years to include the effect of weather and seasons on the rutting of granular pavements. The properties of the pavement material were then used in mechanistic analysis using finite element method for calculation of failure stresses and strains, and this leads to the mechanistic-empirical basis for design. Finally, the framework of the proposed method contributes to LVR pavement design procedures mainly due to its simplicity. © 2014 Taylor & Francis.